Evaluation of eight cephalosporins in hamster colitis model. - Ebright, J R (1981)
Eight commonly used cephalosporins were evaluated in the hamster colitis mode. They were all found to cause hemorrhagic cecitis and death within 10 days of being given as subcutaneous or oral challenges. Necropsy findings were indistinguishable from clindamycin-induced cecitis. Bacteria-free cecal filtrate obtained from hamsters dying of cephalosporin-induced cecitis contained toxin similar or identical to hat produced by Clostridium difficile isolated from the cecum of a hamster. Daily oral administration of poorly absorbed cephalosporins protected hamsters from clindamycin-induced cecitis and death as long as the cephalosporins were continued. The absorbable cephalosporins were ineffective in protecting hamsters from clindamycin-induced cecitis. This difference probably relates to the lower concentrations of absorbable cephalosporins maintained in the ceca of the hamsters. The possible correlation of these findings to human cases of cephalosporin-induced pseudomembranous colitis is discussed.